2014
DOI: 10.1016/j.actamat.2013.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modeling of the densification process in silica glass under hydrostatic compression

Abstract: The mechanical response of amorphous silica (or silica glass) under hydrostatic compression for very high pressures up to 25 GPa is modelled via an elastic-plastic constitutive equation (continuum mechanics framework). The material parameters appearing in the theory have been estimated from the ex situ experimental data from Rouxel et al. [Rouxel T, Ji H, Guin JP, Augereau F, Rufflé B J Appl Phys 2010;107(9):094903]. The model is shown to capture the major features of the pressure-volume changes response from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 36 publications
(108 reference statements)
3
46
0
Order By: Relevance
“…However, the response of glass under shear stress is of primary importance to understand threshold of deformation or cracking in glass. For example, these two types of yield criteria are indispensable to obtain the reliable constitutive model for the plastic deformation of glass (Lambropoulos et al, 1997;Lacroix et al, 2012;Keryvin et al, 2014). According to the constitutive models proposed, the yield criterion of glass varies with the type of loading.…”
Section: Methodsmentioning
confidence: 99%
“…However, the response of glass under shear stress is of primary importance to understand threshold of deformation or cracking in glass. For example, these two types of yield criteria are indispensable to obtain the reliable constitutive model for the plastic deformation of glass (Lambropoulos et al, 1997;Lacroix et al, 2012;Keryvin et al, 2014). According to the constitutive models proposed, the yield criterion of glass varies with the type of loading.…”
Section: Methodsmentioning
confidence: 99%
“…This issue was addressed in a study focusing on the modelling of the densification process in a-SiO 2 [74] which demonstrated that accounting for the evolution of the elastic moduli has a marked effect on the result of the modelling. In the case of Vickers, Berkovich or cube-corner indenters, densification is also promoted in regions in contact with the indenter edges, as was shown by Ji et al [70] in the case of Vickers indenter.…”
Section: Search For a Constitutive Lawmentioning
confidence: 99%
“…Newly available data made it possible to have this reference experiment [16,17]. Figure 1 is a comparison between these experiments and the numerical simulation with our model, which is very good in contrast to previous modellings as discussed in [15]. The constitutive equations and the values of all model parameters are not presented in details here for reasons of space and clarity; they can be found in [15].…”
Section: Pressure-induced Densification (Pid)mentioning
confidence: 99%
“…Recently, we have proposed a constitutive model accounting for the different mechanisms in silica glass under pure hydrostatic compression [15]. The salient features of this model are presented here and are schematised on Figure 1.…”
Section: Pressure-induced Densification (Pid)mentioning
confidence: 99%
See 1 more Smart Citation